ANALISIS MANAJEMEN PERSEDIAAN BAHAN BAKU TORTILA RUMPUT LAUT DI INDUSTRI RISQA MULIA DI DESA OLAYA KABUPATEN PARIGI MOUTONG - Ramdania Zafitri; Alimudin Laapo; Sulaiman Sulaiman (Universitas Tadulako, 2015)
This study aimed to ascertaining the amount of the purchase of raw materials economical seaweed, to find out the total cost of supplies economical raw materials seaweed, the number of safety supplies the raw material of seaweed, and for knowing when done reserving back the raw material of seaweed on industrial risqa mulia in Olaya Village Parigi Moutong Regency. An instrument of the data analysis used in this research is economic order quantity ( eoq ), the total cost of the supply, supplies safety and the point of reserving back. The result showed that the number of economical the purchase of raw materials seaweeds that should be done by industry risqa noble in may-august 2014 each as many as 10.69 kg, 8,63 kg, 8 kg, 5,88 kg.The total cost of supplies economical issued in may-august 2014, each of the Rp.142.291 Rp.141.681 Rp.140.452 and Rp.140.804. Supplies security must always be available in a warehouse on industrial risqa noble as many as 0,5 kg. Reserving back the point that needs to be done in may-august 2014 when raw materials at the rate of each as many as 0,89 kg, 0,83 kg, 0,79 kg, and 0,71 kg. Key words : The product tortila seaweed, inventory management.